Madmen and mad money: psychological disability and economics in medieval and early modern literature - Leverton, Tara Juliette Corinna (Department of English Language and Literature, 2018)
In medieval and early modern literature, people with psychological disabilities are commonly represented as nuisances, monsters, and pitiable wretches. This ableist paradigm is partly attributable to the fact that ‘mad’ characters evoke economic anxieties rooted in the socioeconomic climate of the societies in which the respective texts are created. Fictional ‘madmen’ are used as symbols of or scapegoats for economic problems such as rising poverty, price fluctuations, wealth inequality, and evolving inheritance systems. This exacerbates a prevailing belief that the psychologically disabled are undeserving of respect and care, or even that they are less than human. My goal in this dissertation is to document occurrences of this paradigm and analyse how they contribute to the cultural degradation and dehumanisation of people with psychological disabilities. Applying analytical frameworks provided by disability theorists regarding neurodiversity and sanism to medieval and early modern literature, this dissertation will attempt to expand and invigorate the conversation around disabled people’s cultural history. Each chapter finds the seed of its primary focus in scripture – for example, I examine Herod when discussing madness’s effect on the domestic realm and Noah when discussing madness in old age – and each proceeds in a generally chronologically fashion from scripture to medieval literature and finally early modern literature. The medieval texts I analyse are diverse and range from religious poems such as John Gower’s Confessio Amantis (c. 14th century) to the chivalric romances of Chrétien de Troyes. Likewise, the early modern texts under scrutiny include Ben Jonson’s city comedies and Shakespeare’s tragic Timon of Athens (1607). The wide-ranging nature of the texts I examine is intended to indicate that the ableist notions being unpacked are not limited by genre or period